2015
DOI: 10.1039/c5ob01294e
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a catalytic triad increases the glutathione peroxidase-like activity of diaryl diselenides

Abstract: Reactive oxygen species (ROS)-mediated diseased states are of major concern in modern day life. Under oxidative stress conditions, the cellular antioxidants deplete, leading to several biological disorders. Small molecule mimics of different antioxidant enzymes are found to be useful in supplementing the biological systems to detoxify ROS. In this study, we have synthesized a series of amine or amide-based diselenides containing an additional amino group as glutathione peroxidase (GPx) mimetics. These diseleni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Selenium element has proven to be a suitable nuclide in NMR spectroscopy in studies on stability, [40] reactivity, [41,42] chirality, [43,44,45,46,47,48] polymers, [49,50,51] coordination chemistry, [52,53,54,55] and bio-based experiments. [56,57,58,59] The great potential of 77 Se NMR experiments can be attributed to selenium-77 isotope properties, as spin ( 1 = 2 ), natural abundance (7.63%), no quadrupolar moment, magnetogyric ratio (5.12 × 10 7 rad.s À 1 .T À 1 ) and negligible nuclear Overhauser effect (nOe). [60] The wide spectral window of selenium-77 isotope (δ Se = À 700 to + 2200 ppm) provides an accurate form to identify and quantify organoselenium compounds, which the Figure 1 illustrates the resonance ranges of various selenium organic functions.…”
Section: Se Nmr Spectroscopy In Organic Synthesismentioning
confidence: 99%
“…Selenium element has proven to be a suitable nuclide in NMR spectroscopy in studies on stability, [40] reactivity, [41,42] chirality, [43,44,45,46,47,48] polymers, [49,50,51] coordination chemistry, [52,53,54,55] and bio-based experiments. [56,57,58,59] The great potential of 77 Se NMR experiments can be attributed to selenium-77 isotope properties, as spin ( 1 = 2 ), natural abundance (7.63%), no quadrupolar moment, magnetogyric ratio (5.12 × 10 7 rad.s À 1 .T À 1 ) and negligible nuclear Overhauser effect (nOe). [60] The wide spectral window of selenium-77 isotope (δ Se = À 700 to + 2200 ppm) provides an accurate form to identify and quantify organoselenium compounds, which the Figure 1 illustrates the resonance ranges of various selenium organic functions.…”
Section: Se Nmr Spectroscopy In Organic Synthesismentioning
confidence: 99%
“…From a view point of drug design for antioxidant therapy, much effort has been directed for decades toward development of organoselenium compounds [ 2 , 3 , 4 , 5 , 6 , 7 ], which can act as GPx-like catalysts, and also toward elucidation of their catalytic mechanisms [ 8 , 9 , 10 , 11 ]. Various GPx model compounds, most of which are aromatic diselenides (ArSeSeAr), have been developed and their catalytic activities have been evaluated [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. In the meantime, aliphatic and/or aromatic monoselenides (RSeR′) are also known to act as GPx-like catalysts through a unique selenide/selenoxide redox cycle ( Scheme 1 , cycle A), in which selenide 1 is oxidized by H 2 O 2 to the corresponding selenoxide 2 , which is reduced back to 1 by a thiol substrate (RSH) [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the mechanism of the catalytic cycle, the stability or reactivity of the selenenylsulfide and selenenic acid intermediates is not affected much by the additional amino group, while the selenol intermediate further interacts with the protonated additional amino moiety through hydrogen bonding. Moreover, sec-amine-based diselenides showed higher catalytic activity than tert-amine-based diselenides; in contrast, a lower catalytic activity was observed when the amino moiety was substituted by an alcohol, further confirming the important role of the nitrogen in that position [167].…”
Section: Amino-substituted Diselenides: Three Roles For the Price Of Onementioning
confidence: 80%
“…More recently, Bhowmick and Mugesh prepared and studied a set of more complex ortho-substituted, amino-based diphenyl diselenide derivatives (20)(21)(22)(23)(24) [167], because the introduction of an additional secondary or tertiary amino moiety or an oxygen atom on the amino-diselenide scaffold, allows to mimic faithfully the structure of the catalytic triad in the GPx enzyme (Schemes 12, 13). In their combined experimental and theoretical studies, Bhowmick and Mugesh observed that an additional amino group enhances the catalytic activity.…”
Section: Amino-substituted Diselenides: Three Roles For the Price Of Onementioning
confidence: 99%